Innate Immune Cell-Related Pathology in the Thalamus Signals a Risk for Disability Progression in Multiple Sclerosis - Misin Olavi; Matilainen Markus; Nylund Marjo; Honkonen Eveliina; Rissanen Eero; Sucksdorff Marcus; Airas Laura (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Background and Objectives
Our aim was to investigate whether 18-kDa translocator protein (TSPO) radioligand binding in gray matter (GM) predicts later disability progression in multiple sclerosis (MS).
Methods
In this prospective imaging study, innate immune cells were investigated in the MS patient brain using PET imaging. The distribution volume ratio (DVR) of the TSPO-binding radioligand [C-11]PK11195 was determined in 5 GM regions: thalamus, caudate, putamen, pallidum, and cortical GM. Volumetric brain MRI parameters were obtained for comparison. The Expanded Disability Status Scale (EDSS) score was assessed at baseline and after follow-up of 3.0 +/- 0.3 (mean +/- SD) years. Disability progression was defined as an EDSS score increase of 1.0 point or 0.5 point if the baseline EDSS score was >= 6.0. A forward-type stepwise logistic regression model was constructed to compare multiple imaging and clinical variables in their ability to predict later disability progression.
Results
The cohort consisted of 66 patients with MS and 18 healthy controls. Patients with later disability progression (n = 17) had more advanced atrophy in the thalamus, caudate, and putamen at baseline compared with patients with no subsequent worsening. TSPO binding was significantly higher in the thalamus among the patients with later worsening. The thalamic DVR was the only measured imaging variable that remained a significant predictor of disability progression in the regression model. The final model predicted disability progression with 52.9% sensitivity and 93.9% specificity with an area under the curve value of 0.82 (receiver operating characteristic curve).
Discussion
Increased TSPO radioligand binding in the thalamus has potential in predicting short-term disability progression in MS and seems to be more sensitive for this than GM atrophy measures.